Orientation measurement with gyrotheodolite - Bezdíček, Vladimír; Dandoš, Rostislav; Konečný, Miroslav; Kotrbanec, Juraj; Král, Tomáš; Wlochová, Andrea (Geodesy and Cartography, 2018)
The article deals with the principle of using gyrotheodolite in connection and orientation measurements. It describes orientation measurements with gyrotheodolite, provides basic information about the device and explains how it works. The first part describes gyrotheodolite and methods of determining astronomical true north. The workflow for measurement and subsequent data processing is described below. In the second part, two orientation measurements are described and processed. Finally, the accuracy achieved and the possibility to use the device for activities other than mine measurement are assessed.